A holistic sustainability assessment of organic (certified and non-certified) and non-organic smallholder farms in Kenya - Juliet Wanjiku Kamau; Christian Schader; Lisa Biber-Freudenberger; Till Stellmacher; David M. Amudavi; Jan Landert; Johan Blockeel; Cory Whitney; Christian Borgemeister (Environment, Development and Sustainability, 2021)
The introduction of organic farm management practices in sub-Saharan Africa could act as a lever for supporting regional sustainable development. In this study, we sought to assess the sustainability performance of organic (certified and non-certified) and non-organic farms in the dry Kajiado County and the wet Murang'a County in Kenya, based on four sustainability dimensions: Good Governance, Environmental Integrity, Economic Resilience and Social Well-Being. We collected household survey data from 400 smallholder farms, which were formally characterized into five types (mixed organic and conventional, certified organic, organic, conventional, and subsistence farms). We used multivariate analysis of variance, linear fixed-effects and general linear models to examine differences in sustainability performance. Model results indicate that all farms lack reliable farm management information and that only limited knowledge, skills and social security exist for farmers and farm workers. Comparison of the five farm types indicates no significant differences in their sustainability performance. Nonetheless, certified organic farms had better sustainability performance than non-certified farms due to higher economic resilience, environmental integrity, better support and training for workers. However, except for avoiding the use of agrochemicals in certified farms, there is relatively little difference in the farm management practices across farm types. Our results also indicate that farms in Murang'a were more sustainable than those in Kajiado due to better regional land-tenure security and conflict resolution mechanisms, soil and water conservation measures, and farm commercial viability. Nonetheless, unlike Kajiado, farms in Murang'a showed a tendency toward poor animal husbandry practices which affects overall animal welfare, limited credit uptake and market involvement. The results of this study can support decision making to identify appropriate interventions for improving sustainability in smallholder farms.
Keywords: 330; SAFA guidelines; Organic agriculture; Sub-Saharan Africa; Certification; Indicators